Coda: Reading Duncan Reading Stein - Steve McCaffery (Sillages Critiques)
Investigating the Robert Duncan Notebooks held in the Poetry Collection at the University at Buffalo, this paper offers insights into the various manners in which Duncan read Gertrude Stein revealing his predilections, and comparisons. Most significantly we note emerging a germinal Poetics of Incoherence and Disintegration, and a wholesale attack on grammatical order that aligns both Stein and Duncan himself with the avant-garde trajectories of Hugo Ball’s “poetry without words” and Marinetti’s “words in freedom.”